(untitled) (Research, Society and Development, 2022)
New sources of dietary fiber have been prospected for their importance in promoting human health, however technical points of physicochemical quality and functional properties must be established as criteria for indication for use. Agro-industrial fibrous residues can potentially present characteristics of interest as a source of dietary fiber. In this sense, the fibers obtained after the extraction of starch from arrowroot (Maranta arundinacea L.) can potentially present properties of interest, in addition to advantages such as good sanitary conditions and low cost. Thus, the objective of this research was to carry out the determination of these properties in arrowroot fibers (common variety) obtained under laboratory conditions, being compared with commercial wheat fiber and cassava. The results presented indicate the potential use of fibers in human food, with characteristics similar to commercial fibers. Among the main highlights are: light color (61.53% clarity), with shades of red and yellow. The content of phenolics similar to wheat fiber, showing antioxidant action. The caloric value was 228 kcal 100 g-1, with a low content of lipids (2.23 g 100 g-1), protein (4.9 g 100 g-1) and ash (3.49 g 100 g-1). Neutral detergent fiber 38 g 100 g-1 and acid detergent fiber 23 g 100 g-1 profile classifies it as a fiber source and functional food for healthy adults.